(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Background: Mosquito coil (MC) is widely used to repel mosquitoes in order to prevent malaria in many malaria-endemic countries. Although we are fully aware and concerned about carbon monoxide (CO) and its toxicity, exposure to CO from common, though occult sources like MC smoke is often overlooked. Equally, the adverse health effects, especially to the brain, are usually underestimated. Objective: To assess the effects of exposure to CO from MC smoke inhalation on spatial memory in mice. Methods: Sixteen, adult, male, mice, were randomly assigned to either the experimental or the control group; each having 8 mice. The experimental group was exposed to the MC smoke (Wavetide, China) that was allowed to burn inside the gas chamber (75 cm x 50 cm x 50 cm) for 15 minutes, daily, for 14 days. Digital CO meter (PCMM05 Pyle) was used to measure the amount of CO and Barnes maze protocol to assess the spatial memory. Results: Our results indicate that burning MC for 15 minutes produced up to 312 parts per million (ppm) of CO and raised the blood carboxy-hemoglobin (COHb) level by 15.8%. This is higher than the WHO recommended limit (<100 mg/m3 or 87 ppm for 15 min.) of CO exposure and the %COHb level of <2%. Mosquito coil smoke was also associated with impaired spatial memory. However, the dose and duration of exposure did not significantly affect weight gain in the mice. Conclusion: Although widely used to prevent malaria, MC could serve as a potential source of CO and other neurotoxins that could be harmful to the brain; the use and toxicity of which is mostly overlooked even by the public health professionals.